Analysis of the Impact of Limited Access to Housing on Socio-Economic Conditions in Jakarta Slums DKI Jakarta - Setyo Cahyono, Ragil; Adianto, Joko (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2022)
This study aims to analyze the impact of limited access to housing on socioeconomic conditions in DKI Jakarta slums. DKI Jakarta's slums are home to many low-income people, and limited access to housing in these areas has a significant impact on their socioeconomic conditions. The method used in this research is a qualitative method with a case study design, and data was collected through in-depth interviews with informants selected through a snowball sampling technique. The results show that limited access to housing has an impact on the socioeconomic status of low-income residents in the slums of DKI Jakarta. People living in areas with limited housing access have lower income levels, lower education levels, and lower health levels. In addition, access to health services is also more limited. To improve the socio-economic conditions of low-income people in slums in DKI Jakarta, efforts are needed to improve housing access. Some of the efforts that can be made include the development of affordable and environmentally friendly housing, as well as providing access to basic infrastructure such as roads, clean water, and adequate sanitation. This research also found that urbanization and land constraints contribute to the emergence of slums and limited access to housing. In addition, this research shows that the construction of decent housing can have positive impacts on low-income communities, such as increased employment and economic capacity, as well as improved education and health. Therefore, improving access to housing should be a priority in efforts to improve socioeconomic conditions in DKI Jakarta slums.